Fatigue life estimation of single lap adhesive joints using a critical distance criterion: An equivalent notch approach. (February 2021) - Sousa, F. Castro; Akhavan-Safar, A.; Goyal, R.; da Silva, L.F.M.
Abstract: The fatigue life prediction of adhesive joints still remains a challenging issue. Given the increasing need for safer and more efficient industrial bonded structures, the development of simple fatigue design methodologies is of primordial relevance. In this work, a model based on the S–N approach for the estimation of the fatigue life of single lap adhesive joints with different geometries is proposed. Steel substrates and an epoxy adhesive were considered to manufacture joints with different overlap lengths, adherend thicknesses and widths. The joints were tested under static and fatigue loading conditions. A critical distance approach based on a recently developed effective stress is proposed to deal with the effect of stress concentrations exhibited by this type of joints. The results showed a good correlation between the experimental and the estimated fatigue lives. Highlights: A simple and accurate fatigue model able to predict fatigue life of SLJs with different configurations is developed. The developed method is based on the concepts of the S–N approach and the theory of critical distances. An Equivalent Notch Approach (ENA) is adopted to determine the critical distance. The influence of the mesh size on the proposed fatigue model is almost negligible.